Imperative Sentence Analysis Of The Ministry Of Education's Short Film Series In Teaching Material Recommendation Imperative Sentences Based On Pancasila Learner Profile - Hakim, Titik Dwi Ramthi; Mardliyah, Ummu Zulfa (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Many problems in teaching and learning activities occur due to the ineffectiveness of the media used. Learning media is anything that can be used as an intermediary from the sender (educator) to the recipient (students) so that the learning process occurs. Profil pelajar pancasila supports the independent curriculum program for Pancasila student profiles through its YouTube channel short film series "Cerdas berkarakter” contain profil pelajar pancasila of the Republic of Indonesia". Learning media that can contain dimensions of Pancasila student profiles that can be used for learning media, especially Indonesian, imperative sentence material used in this study. Because it includes the dimensions of the Pancasila student profile, many moral values can be drawn that are relevant to students' daily lives. The approach used in this research is a qualitative approach. The method used is descriptive. This study uses a descriptive method, which is divided into two stages, namely the data collection method and the data analysis method. The total results of imperative sentences from all short film series are 67 imperative sentences consisting of 19 subtle imperative sentences, 1 imperative imperative sentence of omission, 17 imperative sentences of request, 12 imperative sentences of invitation, and 18 imperative sentences of prohibition. There are many messages that are relevant to everyday life in each of the short films on the YouTube channel "Cerdas berkarakteristics of profil pelajar pancasila of the Republic of Indonesia". In particular, the message of caring for others is found in almost all of the short films about Pancasila student profiles.